The Influence of Intensity on Social Media Instagram Against Social Comparison With Group Competition as Moderator - Nadia Nadia; Nur Fitriany Fakhri; Nur Akmal (PT ARRUS Intelektual Indonesia, 2023)
Adolescents tend to be attracted to groups that are particularly vulnerable to the negative psychological and behavioral outcomes of using Instagram social media. Since adolescent behavior is easily shaped by the social context in which they are located, it is likely that friends may be the key that has a strong influence on the behavioral outcomes that adolescents develop from social media use. Given the concerns about the negative consequences of using Instagram social media by teenagers, this study aims to find out how the intensity of Instagram social media use affects social comparison moderated by group competition. The research method used is quantitative research methods. The subjects in this study were adolescents with Instagram social media aged 13-17 years and domiciled in the city of Makassar (N = 334) who were obtained using a cluster random sampling technique. The research data was tested using the Moderation Regression Analysis (MRA) test with the help of the Jamovi 2.3.26 program. The measuring tools used in this study are the social comparison scale, the group competition scale and the intensity scale of social media use. The results showed that there was no significant effect between the intensity of using Instagram social media on social comparison moderated by group competition (p) of 0.704 (p > 0.05). This research offers additional insight into how it is important to understand that the behavior exhibited by adolescents is also strongly shaped by their peer environment. This means that not all adolescents will be affected by social media use to the same degree, but those who face social pressure from their peers are more susceptible to social comparisons.